ANALYSIS OF INTRINSIC ELEMENTS OF THE NOVEL IN MIHRAB CINTA BY HABIBURRAHMAN EL SHIRAZY - Elvionika, Hakiki (CV. Fahr Publishing, 2023)
This research uses descriptive research methods. The data source used in this research is the novelette Dalam Mihrab Cinta. The data analysis technique used is descriptive analysis. From the results of the analysis, it was found that the intrinsic elements of the work consist of a calm religious theme because it discusses natural religious issues, the message conveyed by the author is in the form of a moral message that we should not slander people because slander is an act that is very detrimental to ourselves and others, the plot used in the novelette In Mihrab Cinta this is a mixed plot because the series of stories are interconnected with each other, the story characters are Syamsul Hadi' and Nadia. Other figures (extras) are: Pak Kiai, Burhan, Pak Bambang (Syamsu's father), Bu Bambang (Syamsul's mother), Nadia, his two older brothers, Pak Abbas, Silvie, Dalmayanti, Pak Broto, Della, Pak Heru, Silvie's father , Pak Anuar, Pak Utsman, Bu Heru, Doddy Alfad, Mas Budi, The setting of the novelette Dalam Mihrab Cinta is in several places, including, at Islamic boarding schools, at home, Central Java, Upper Semarang, Jakarta, at the mosque, Villa Gracia , Flamboyan 19, Flamboyan 17, in front of the house, at Kediri Police Station, Cipuput market. Setting time: noon, before Asr, ten minutes, ten minutes later, already one week, next week, that afternoon, one year, one month, one year, in the evening, Asr, Maghrib time, Sunday morning, end of last month, five o'clock afternoon, Bakda Maghrib, the next day, the last day of the month of Shaban, the holy month of Ramadan, after Maghrib, the 8th of Rahmadhan. The results of this study are expected to provide information and benefits to other writers in writing literary works.